NAFTA and the gender wage gap - Shushanik Hakobyan; John McLaren (W.E. Upjohn Institute for Employment Research, 2017)
Using U.S. Census data for 1990-2000, we estimate effects of NAFTA on U.S. wages, focusing on differences by gender. We find that NAFTA tariff reductions are associated with substantially reduced wage growth for married blue-collar women, much larger than the effect for other demographic groups. We investigate several possible explanations for this finding. It is not explained by differential sensitivity of female-dominated occupations to trade shocks, or by household bargaining that makes married female workers less able to change their industry of employment than other workers. We find some support for an explanation based on an equilibrium theory of selective non-participation in the labor market, whereby some of the higher-wage married female workers in their industry drop out of the labor market in response to their industry's loss of tariff. However, this does not fully explain the findings, so we are left with a puzzle.
Keywords: F16; F13; J31; 330; NAFTA; gender wage gap; local labor markets